A formação do professor de educação física da UFSM: elementos que possibilitem a atuação docente com vistas ao processo de inclusão de pessoas com deficiência/necessidades educacionais especiais - Patias, Bhianca Conterato (2023)
This doctoral research is linked to the Postgraduate Program in Education at the Universidade Federal de Santa Maria, Research Line in Special Education, Inclusion, and Difference, Grupo de Estudos e Pesquisas em Psicologia da Educação e Educação Inclusiva-GEPEIN. The general objective of this thesis was to analyze the elements in the graduation of Physical Education teachers from the Center of Physical Education and Sports at the Universidade Federal de Santa Maria that enable teaching practices aimed at the inclusion process of people with disabilities / special educational needs. To achieve the proposed objectives, this investigation falls within the scope of qualitative research, with data collection carried out through document analysis (CELLARD, 2010) and semi-structured interviews (MINAYO, 2012). Subsequently, data analysis took place through the content analysis technique (BARDIN, 2001).Fifteen professors from the Physical Education teaching program at the Center for Physical Education and Sports at the Universidade Federal de Santa Maria, as well as nine former teachers from this program, were interviewed. As results, it was observed that the former teachers of the Physical Education teaching program at CEFFD/UFSM encounter difficulties in developing their teaching practices when faced with a class that includes students with disabilities/SEN. These difficulties are related to how to create a lesson plan, how to assess, how to include everyone in the class without excluding anyone. Additionally, they believe that the program needs more disciplines that focus on this topic and suggest that existing disciplines incorporate content related to the inclusion of individuals with disabilities/SEN, such as collective sports disciplines. Regarding the program's faculty, some incorporate content related to inclusion by presenting situations where students must think and seek alternatives to conduct a class, as well as promoting discussions when the topic arises through student demands. These faculty members also face challenges in teaching in higher education settings with students with disabilities, as many were not prepared for it. This suggests a need to enhance the current training and provide continuous training for educators. In conclusion, the contents that address the theme of inclusive Physical Education are still limited, requiring a greater number of disciplines that cover the topic, and existing disciplines should include elements that connect the specific field of physical education with the development of individuals with disabilities/SEN.